Strong inflammatory responses and apoptosis in the oviducts of egg-laying hens caused by genotype VIId Newcastle disease virus. Issue 1 (December 2016) - Li, Ruiqiao; Guo, Kangkang; Liu, Caihong; Wang, Jing; Tan, Dan; Han, Xueying; Tang, Chao; Zhang, Yanming; Wang, Jingyu
Abstract Background Newcastle disease virus (NDV) can cause serious damage to the reproductive tracts of egg-laying hens and leads to egg production and quality reduction. However, the mechanism of severe pathological damage in the oviducts of egg-laying hens after NDV infection has not been fully elucidated. In this study, the correlation between the primary pathological lesions and viral load in the oviducts of egg-laying hens infected with the velogenic genotype VIId NDV strain was evaluated by pathological observation and virus detection. Subsequently, apoptosis, the expression of immune-related genes and lymphocyte infiltration into the infected oviducts were determined to explore the potential causes of the pathological changes. Results A higher viral load and severe tissue lesions and apoptotic bodies were observed in the oviduct of NDV-infected hens compared with the control. Immune-related genes, including TLR3/7/21, MDA5, IL-2/6/1β, IFN-β, CXCLi1/2, and CCR5, were significantly upregulated in the magnum and uterus. IL-2 presented the highest mRNA level change (137-fold) at 5 days post infection (dpi) in the magnum. Infection led to CD3+ CD4+ and CD3+ CD8α+ lymphocyte infiltration into the magnum of the oviduct. A higher viral load was found to be associated with pathological changes and the elevated expression of proinflammatory cytokines in the NDV-infected hens. Conclusions Our results indicate that the severe lesions and apoptosis in the oviducts of egg-laying hens caused by genotype VIId NDV strains are associated with the excessive release of inflammatory cytokines, chemokines and lymphocyte infiltration, which contribute to the dysfunction of the oviducts and the decrease of egg production in hens.